Psychological and socio-economic considerations associated with consuming CSD: A Study - Rasel, Md Khairul Alam; Himel, Shadrul Hassan (The National University Journal of Humanities, Social Sciences and Business Studies, 2023)
people of all ages love to have carbonated soft drinks except those who have some serious health issues. Understanding the consumption pattern of the Generation Y (a generational cohort) would be high priority to the marketer because of the significant characteristics of that segment. Therefore, this paper examines the underlying positive psychological and socio-economic causes which drive the Generation Y to consume carbonated soft drinks. A sample of 257 respondents were taken on the basis of judgemental sampling for this study. Regression analysis and factor analysis were administered to analyse the collected data. This research reveals that Refreshing nature of Carbonated soft drinks (CSD), Meeting with friends, family and co-workers, Taste of CSD, Sweetness nature of the CSD are remarkable underlying positive psychological and socio-economic considerations which drive Generation Y to consume carbonated soft drinks. NU Journal of Humanities, Social Sciences & Business Studies Vol. 7 & 8, No.2 & 1, July 2021 - December 2022 p. 57-74